2013
DOI: 10.1021/om4007399
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Triosmium Carbonyl Cluster Complexes with Bridging Aryl Ligands: Structures, Bonding, and Transformations

Abstract: For the calculations on 2, geometry optimized calculations were performed with ADF2012 program 24 by using the PBEsol functional 1 with scalar relativistic correction and valence quadruple-ζ + 4 polarization, relativistically optimized (QZ4P) basis sets for osmium and gold and valence double-ζ function (DZ) basis sets for the phosphorus, carbon, oxygen, and hydrogen atoms with no frozen cores. The molecular orbitals for 2 and their energies were determined by a geometry optimized calculations that were initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…An ORTEP diagram of the molecular structure of 3 is shown in Figure 2. In 3,the naphthyl ligand serves as athree-electron donor, thus the rhenium atoms are formally electronically saturated and as ar esult, the Re À Re bond distance,3 .0531(3) , is significantly longer than that in the unsaturated 2.Asimilarly coordinated m-h 2 -naphthyl ligand was recently structurally characterized as one of two isomers of the triosmium complex [Os 3 (CO) 10 [7] Most interestingly,itwas found that 1 reacts with C 6 D 6 to produce its deuterated equivalent [D 6 ]-1 in quantitative yield within 11 hours at 60 8 8C[ Equation (3)]. Then aphthyl ligand was formed by the elimination of benzene from 1 and the oxidative addition of naphthalene at aC À Hb ond at the 2-position.…”
mentioning
confidence: 99%
“…An ORTEP diagram of the molecular structure of 3 is shown in Figure 2. In 3,the naphthyl ligand serves as athree-electron donor, thus the rhenium atoms are formally electronically saturated and as ar esult, the Re À Re bond distance,3 .0531(3) , is significantly longer than that in the unsaturated 2.Asimilarly coordinated m-h 2 -naphthyl ligand was recently structurally characterized as one of two isomers of the triosmium complex [Os 3 (CO) 10 [7] Most interestingly,itwas found that 1 reacts with C 6 D 6 to produce its deuterated equivalent [D 6 ]-1 in quantitative yield within 11 hours at 60 8 8C[ Equation (3)]. Then aphthyl ligand was formed by the elimination of benzene from 1 and the oxidative addition of naphthalene at aC À Hb ond at the 2-position.…”
mentioning
confidence: 99%
“…Two of the Au(PPh 3 ) groups form a mutually bonded pair on the Ru1-Ru2-Ru3 face and Ru2-Ru3 edge of the square pyramid, Au1-Au2 = 2.8277(6) Å, similar to that found in 9. An additional Au(PPh 3 ) group, Au4, is found along the Ru4 -Ru5 edge of the Ru 5 square base and for the fourth Au(PPh 3 ) group, atom Au3, is asymmetrically bonded across the square base and includes bonding to the interstitial carbido ligand C0, Ru2-Au3 = 3.1831 9 11, Ru1-Ru4 = 2.8498 10, Ru2-Ru5 = 2.8148 11Ru2-Ru3 = 3.0316 (10),Ru3-Ru4 = 2.7968 10, Ru4-Ru5 = 3.0933 10, Ru1-Au1 = 2.8728 9, Ru2-Au1 = 2.8609 9 8, Au3-C0 = 2.126 (8).…”
Section: Resultsmentioning
confidence: 99%
“…Eqs. (1) -(3) [7][8][9]. In some cases, the aryl ligands have adopted unusual bridging coordination modes that can result in interesting physical and chemical properties, such as hindered rotation about the metal-metal bond [10].…”
Section: Introductionmentioning
confidence: 99%
“…Examples with terminally-coordinated tin ligands include Au(PMe 2 Ph) 2 (SnCl 3 ), 1, Au -Sn = 2.881(1) Å [6] and Au(PPh 3 )[Sn{N(p-tol)SiMe 2 } 3 SiMe], 2, [7], see Scheme 1. We have recently found that aryl containing gold phosphine complexes, Au(PPh 3 )Ar, Ar = Ph, Np, Py, react with certain dirhenium [11] and triosmium [12] carbonyl complexes to yield electronically unsaturated complexes containing bridging aryl ligands. In the present work, we have investigated the reaction of Au(PPh 3 )Ph with HSnPh 3 .…”
Section: Introductionmentioning
confidence: 99%